Permasalahan Pendidikan dan Upaya Peningkatannya di Desa Niopanda Kecamatan Kotabaru Kabupaten Ende - Nona Tiara, Angela Marici; Nona Lehan, Leny Maria; Syahrun, M. (Universitas Syiah Kuala, 2025)
This study aims to 1). Identify educational issues in Niopanda Village, Kotabaru Subdistrict, Ende Regency, and 2). Describe efforts to improve education in Niopanda Village, Kotabaru Subdistrict, Ende Regency. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The results of the study show that the main challenges in education in Niopanda Village include limited school facilities and infrastructure, a shortage of qualified teachers, low community participation, and economic and cultural factors that affect the continuity of children's education. Recommendations include improving facilities and infrastructure, recruiting and training teachers, community education awareness programs, family economic support, and the use of technology. These findings are expected to serve as a reference in formulating policies to improve the quality of education in rural areas.